Assessment of spiritual care competency among nurses in Sultan Ahmad Shah Medical Centre: a cross-sectional study - Abdul Rashid, Nor'ain; Mohd Asri, Mohamad Ashraf; Othman, Hamidah; Nur Hidayati, Nur Hidayati (Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, 2026)
Spiritual care, which is considered a significant part of holistic nursing care, involves nurses to fulfil the patients’ emotional, psychological, and spiritual needs. Spiritual care competency is an important aspect in maximising the quality of care to the patients and encouraging professionalism. This study aimed to assess the level of spiritual care competency among nurses in Sultan Ahmad Shah Medical Centre (SASMEC), and the association between sociodemographic factors with the level of spiritual care competency. This was a quantitative cross-sectional study conducted among 155 nurses from SASMEC IIUM using self-administered questionnaires, which included sociodemographic factors, the Spiritual Care Competency Scale (SCCS). Descriptive statistics, Chi Square Test, and Pearson Correlation Test were used in data analysis via SPSS version 27. The majority of the nurses in SASMEC IIUM perceived high levels of competency (99.4%). The highest mean difference among the domains were assessment and implementation of spiritual care (MD=12.368), and personal support and patient counselling (MD=12.368) while the lowest mean difference was communication (MD=4.155). Furthermore, there was no significant relationship between spiritual care competence and sociodemographic factors (age, marital status, educational level, nurses’ experience, race, religion, and previous participation in training spiritual care programs), except for gender (p<0.05) in which females acquired higher competency level than males. This study may help healthcare organizations and educational institutions to develop and implement strategies in enhancing and polishing the standard of spiritual care among nurses. Future studies are recommended to explain the natural association between sociodemographic factors and spiritual care competence.